2016
DOI: 10.1002/ijc.30071
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms for predicting prognostic value of inflammatory biomarkers in colorectal cancer patients after radical resection

Abstract: Increasing evidence indicates that inflammation plays a vital role in tumorigenesis and progression. However, the prognostic value of inflammatory biomarkers in colorectal cancer (CRC) has not been established. In this study, a retrospective analysis was conducted in patients with CRC in Fudan University Shanghai Cancer Center (FUSCC) between April 1, 2007 and April 30, 2014, and 5,336 patients were identified eligible. Neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), lymphocyte-to-mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
152
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(159 citation statements)
references
References 42 publications
(83 reference statements)
6
152
1
Order By: Relevance
“…As a result, a total of nine studies comprising 8626 patients with CRC fulfilled all of the inclusion criteria. [9,10,1521] The PRISMA flow diagram of the study selection process was shown in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, a total of nine studies comprising 8626 patients with CRC fulfilled all of the inclusion criteria. [9,10,1521] The PRISMA flow diagram of the study selection process was shown in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…When reviewing the literature, there are different cut-off values for biomarkers, ratios and scores based on cancer type and study population/area. Thus, it is difficult to create standardized cut-offs that can be used worldwide, even within a single cancer type 19,48,49 . Second, this dataset included only patients who underwent surgical resection for OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, nomograms have been constructed in a variety of cancers, and some of them have been found to be more reliable prediction than the traditional staging system 23, 32-34. Moreover it has been validated to compare favorably to the traditional TNM staging systems in many cancers, and thus have been identified as an alternative or even a new standard 22, 35, 36. A number of studies also found that in patients with NSCLC, nomograms were accurate to predict the risk of a node's involvement 37, 38, the individual risk of developing metastasis to the brain and had strong performance in individualize patient decision making 39.…”
Section: Discussionmentioning
confidence: 99%